Pengaruh Discovery Learning Terhadap Motivasi Belajar Mahasiswa Prodi Manajemen di Universitas Nahdlatul Ulama Al Ghazali Cilacap - Yudi Agus Setiawan; Mutia Pamikatsih; Neti Endang Wahyuni (Fakultas Ekonomi Universitas 45 Surabaya, 2025)
At Nahdlatul Ulama Al Ghazali University Cilacap, one of the learning models is called Discovery Learning. This learning model emphasizes the active involvement of students in the learning process. This is because this model is centered on students discovering concepts and knowledge on their own through exploration and research. The stages of the discovery learning model involve the lecturer preparing teaching materials in the form of PowerPoint presentations or videos, after which students actively engage in learning activities and can identify areas where they need to improve their understanding and skills. The purpose of this research is to determine the effect of discovery learning on learning motivation. The research method used is a quantitative method because the research data is in the form of numbers and the analysis uses statistics. The analysis used is linear regression analysis with a population of Management program students. The number of samples used amounted to 34 students. The data collection technique involved tests and questionnaires using a Likert scale. From the results of the normality test and linearity test, the sig values of 0.200 and 0.177 indicate that the data are normally and linearly distributed. Based on the linear regression test, a t-value of 3.296>t-table 2.037 with a regression coefficient of 0.331 indicates that there is an influence between variable x (discovery learning) and variable y (learning motivation).